2017
DOI: 10.1186/s12974-017-0853-2
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α promotes extracellular vesicle release in mouse astrocytes through glutaminase

Abstract: BackgroundExtracellular vesicles (EVs) are membrane-contained vesicles shed from cells. EVs contain proteins, lipids, and nucleotides, all of which play important roles in intercellular communication. The release of EVs is known to increase during neuroinflammation. Glutaminase, a mitochondrial enzyme that converts glutamine to glutamate, has been implicated in the biogenesis of EVs. We have previously demonstrated that TNF-α promotes glutaminase expression in neurons. However, the expression and the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…EVs can be found in interstitial fluid, cerebrospinal fluid (Vella et al, 2008), circulating blood (Suetsugu et al, 2013), and primarily assert biological function through delivering cytokines, nucleic acids, lipids, and proteins to nearby or distant cells, suggesting that they play an important role in cell-to-cell communication (Thery et al, 2006). EV secretion is increased during neuroinflammation; our previous studies, along with others', have suggested that EVs fuel pathogenic processes in the brain during neuroinflammation (Gupta and Pulliam, 2014;Huang et al, 2018;Wang et al, 2017;Wu et al, 2015;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…EVs can be found in interstitial fluid, cerebrospinal fluid (Vella et al, 2008), circulating blood (Suetsugu et al, 2013), and primarily assert biological function through delivering cytokines, nucleic acids, lipids, and proteins to nearby or distant cells, suggesting that they play an important role in cell-to-cell communication (Thery et al, 2006). EV secretion is increased during neuroinflammation; our previous studies, along with others', have suggested that EVs fuel pathogenic processes in the brain during neuroinflammation (Gupta and Pulliam, 2014;Huang et al, 2018;Wang et al, 2017;Wu et al, 2015;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Because our previous findings indicate that GLS1 is a key enzyme in exosomes release of glial cells including microglia and astrocytes in vitro (16,17), we examined whether or not the alteration of exosome release in focal cerebral ischemic brains is mediated by GLS1. NTA demonstrated that GLS1 inhibition by CB839 administration significantly reduced the concentration of exosome in ischemic rat brains vs. the DMSO-treated ischemia group (Figure 5A).…”
Section: Gls1 Mediates Pro-inflammatory Exosome Releasementioning
confidence: 99%
“…TNF-α is implicated across a range of autoimmune conditions and diseases and has received great attention as a therapeutic target [ 23 ]. Organ-specific increases in TNF-α have been shown to induce innate immune cell infiltration and activation, tissue resident cell activation, and pro-inflammatory cytokine secretion [ 24 , 25 , 26 ]. In particular, the blockade of TNF-α has been shown to ameliorate the inflammatory symptoms of RA and attenuate the extent of joint and cartilage erosion [ 27 ].…”
Section: Cytokines Inflammation and Autoimmunitymentioning
confidence: 99%